Employee Productivity in Weed Control on Palm Oil Plantations - Ardian Alexius Aven; Muhamad Yazid Bustomi; Arief Rahman; Ernita Obeth; Rossy Mirasari (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
Oil palm cultivation is not only carried out on flat land, but also in hilly areas with challenging topography. Proper plantation management, such as weed control, fertilization, and harvesting in accordance with standards, is essential to maintain quality and production yields. This study aims to (1) determine the differences in the productivity of chemical weed control workers on different plots of land (2) determine the factors that cause differences in the productivity of chemical weed control workers. The data analysis method was descriptive based on the results of field interviews, then using a productivity formula by comparing the number of hectares of work results with the working time for undulating slopes and steep slopes. The respondents in this study were five sprayers working in one of the blocks at PTPN IV Region V Longkali Plantation. The results show that there is a difference in the average productivity of chemical sprayers between the undulating slope class and the steep slope class. The average productivity in the undulating slope class is 0.126 ha/hour, while in the steep slope class it is 0.094 ha/hour. These data indicate that employee productivity is higher when working on land with undulating slopes than on steep slopes. In addition, there are several factors that cause differences in productivity, namely the level of terrain difficulty, water availability, psychology and motivation, topography, and weed conditions on the land.